First-line oxygen therapy with high-flow in bronchiolitis is not cost saving for the health service. Issue 10 (10th April 2020) - Gc, Vijay S; Franklin, Donna; Whitty, Jennifer A; Dalziel, Stuart R; Babl, Franz E; Schlapbach, Luregn J; Fraser, John F; Craig, Simon; Neutze, Jocelyn; Oakley, Ed; Schibler, Andreas
Abstract : Background: Bronchiolitis is the most common reason for hospital admission in infants. High-flow oxygen therapy has emerged as a new treatment; however, the cost-effectiveness of using it as first-line therapy is unknown. Objective: To compare the cost of providing high-flow therapy as a first-line therapy compared with rescue therapy after failure of standard oxygen in the management of bronchiolitis. Methods: A within-trial economic evaluation from the health service perspective using data from a multicentre randomised controlled trial for hypoxic infants (≤12 months) admitted to hospital with bronchiolitis in Australia and New Zealand. Intervention costs, length of hospital and intensive care stay and associated costs were compared for infants who received first-line treatment with high-flow therapy (early high-flow, n=739) or for infants who received standard oxygen and optional rescue high-flow (rescue high-flow, n=733). Costs were applied using Australian costing sources and are reported in 2016–2017 AU$. Results: The incremental cost to avoid one treatment failure was AU$1778 (95% credible interval (CrI) 207 to 7096). Mean cost of bronchiolitis treatment including intervention costs and costs associated with length of stay was AU$420 (95% CrI −176 to 1002) higher per infant in the early high-flow group compared with the rescue high-flow group. There was an 8% (95% CrI 7.5 to 8.6) likelihood of the early high-flow oxygen therapy being cost saving. Conclusions: The use of high-flow oxygen as initial therapy for respiratory failure in infants with bronchiolitis is unlikely to be cost saving to the health system, compared with standard oxygen therapy with rescue high-flow.